Visualizing B cell capture of cognate antigen from follicular dendritic cells - Suzuki, Kazuhiro (The Rockefeller University Press, 2009)
The prominent display of opsonized antigen by follicular dendritic cells (FDCs) has long favored the view that they serve as antigen-presenting cells for B cells. Surprisingly, however, although B cell capture of antigen from macrophages and dendritic cells has been visualized, acquisition from FDCs has not been directly observed. Using two-photon microscopy, we visualized B cell capture of cognate antigen from FDCs. B cell CXCR5 expression was required, and encounter with FDC-associated antigen could be detected for >1 wk after immunization. B cell–FDC contact times were often brief but occasionally persisted for >30 min, and B cells sometimes acquired antigen together with FDC surface proteins. These observations establish that FDCs can serve as sites of B cell antigen capture, with their prolonged display time ensuring that even rare B cells have the chance of antigen encounter, and they suggest possible information transfer from antigen-presenting cell to B cell.